PENGARUH PERBANDINGAN TERIGU DAN PUREE BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KARAKTERISTIK DONAT - Lonika Simbolon, Dinda Tessa; Timur Ina, Putu; Kadek Diah Puspawati, Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPA, 2020)
This research aimed to determine the effect of wheat flour and puree of red dragon fruit ratio on the characteristics of donut and obtain a ratio of wheat flour and puree of red dragon fruit which able to produce donut with the best characteristics. The Completely Randomized Design was used in this researched with the treatment ratio of wheat flour and puree of red dragon fruit which consisted of five levels, such as 100% : 0%, 90% : 10%, 80% : 20%, 70% : 30%, 60% : 40%. The treatment was repeated 3 times to obtain 15 units of experiment. The datas were analyzed by analysis of variance and if the treatment had a significant effect, the Duncan Multiple Range Test were performed. The results showed that ratio of wheat flour and puree of red dragon fruit had a significant effect on water content, anthocyanin content, antioxidant activity, (L*), (a*), (b*), color (hedonic and scoring), texture (hedonic and scoring), tasted (hedonic), and overall acceptance (hedonic) and had no significant effect on odor (hedonic). Ratio of 60% wheat flour : 40% puree of red dragon fruit produced the best characteristic of donut, with the following criteria: 23.17% water content, 12.85mg/100g anthocyanin content, 64.58% antioxidant activity, 31.13 (L*), 41.33 (a*), 14.33 (b*), very red color and liked, odor and taste liked, very soft texture and liked, and overall acceptance liked.